Death of the covenant code: capital punishment in old Greek exodus in light of Greco-Egyptian law - Korytko, Joel (Journal for the study of Judaism / Supplements, 2023)
"Many laws in the Old Greek translation of the Covenant Code do not say the same thing as the Hebrew text. In the past, various idiosyncrasies in the Greek translation of laws that involve the death penalty had been glossed over and considered stylistic variations or grammatical outliers. However, when the text-linguistic features of the Greek translation are compared to contemporary literary, documentary, and legal Greek sources, new readings emerge: cursing a parent is no longer punishable by death; a law about bestiality becomes a law about animal husbandry; the authority of certain legal commands is deregulated. This work explores these and other new readings in comparison with contemporary Greco-Egyptian law"--